1985
DOI: 10.1679/aohc.48.117
|View full text |Cite
|
Sign up to set email alerts
|

Stratified laminae fenestratae (alveolus fenestratus endothelialis) in the glomerular capillaries of the mouse kidney.

Abstract: Summary. The fine structure of the stratified lamina f enestrata of the mouse glomerulus was described in detail in both transmission and scanning electron microscopy. We propose to name the extremely developed structure of the stratified lamina fenestrata as the alveolus endothelialis. It consists of numerous small irregular spaces partitioned by thin cytoplasmic processes. Individual spaces communicate with each other through the fenestra surrounded by the cytoplasmic partitions.This structure occurs not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…As capillary walls can be divided into peripheral and mesangial regions [36], only peripheral portions where glomerular basement membranes and capillary walls show parallelism were considered. We found that the quantification in the mesangial portions is not comparable to the peripheral parts as the predominant amount of mesangial endothelium is not fenestrated whereas on the other hand there are parts with increased fenestration (as described as “alveolus fenestratus endothelialis” by Kondo et al, [37]. Thus, this endothelium is morphologically not comparable to the single layered endothelium in the peripheral portions so that applying the same quantification method would not be admissible (Fig.3A–B).…”
Section: Methodsmentioning
confidence: 86%
“…As capillary walls can be divided into peripheral and mesangial regions [36], only peripheral portions where glomerular basement membranes and capillary walls show parallelism were considered. We found that the quantification in the mesangial portions is not comparable to the peripheral parts as the predominant amount of mesangial endothelium is not fenestrated whereas on the other hand there are parts with increased fenestration (as described as “alveolus fenestratus endothelialis” by Kondo et al, [37]. Thus, this endothelium is morphologically not comparable to the single layered endothelium in the peripheral portions so that applying the same quantification method would not be admissible (Fig.3A–B).…”
Section: Methodsmentioning
confidence: 86%
“…This is possible because of the unique properties of glomerular endothelial cells. In healthy glomeruli, most of the endothelial surface is extremely flat and contains many transcellular pores, or fenestrae [1,2]. The extent of endothelial fenestration may control the available glomerular basement membrane surface for plasma filtration.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Distinct from the common endothelium, healthy glomerular endothelium is extremely flat and densely perforated by fenestrae, which has been defined as transendothelial cell pores. 20,21 Recent studies have described the ultrastructure of a glycoprotein coat within the fenestrae of glomerular endothelial cells. 22,23 This glycoprotein coat with a negatively charged layer close to the blood compartment accounts for retention of 90-95% of albumin.…”
Section: Discussionmentioning
confidence: 99%
“…Daniels and coworkers have shown that the glomerular endothelium significantly influences size selectivity and charge selectivity of the filtration barrier . Distinct from the common endothelium, healthy glomerular endothelium is extremely flat and densely perforated by fenestrae, which has been defined as transendothelial cell pores . Recent studies have described the ultrastructure of a glycoprotein coat within the fenestrae of glomerular endothelial cells .…”
Section: Discussionmentioning
confidence: 99%